THE ROLE OF BHIL, GOND, AND BAIGA TRIBAL ATTIRE IN DEFINING REGIONAL INDIAN FASHION TRENDS - Singh, Shweta; Dubey, Manish; Rana, Kshitij (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The traditional attire of the Bhil, Gond, and Baiga tribes of Madhya Pradesh represents a crucial part of India’s textile heritage and plays a significant role in shaping regional Indian fashion trends. These tribes have preserved their unique textiles, weaving techniques, motifs, and natural dyeing processes, which continue to influence modern designers and sustainable fashion movements. This research examines the impact of these tribal aesthetics on contemporary Indian fashion, the challenges faced by artisans, and the role of globalization, sustainability, and cultural preservation in revitalizing indigenous craftsmanship. Using qualitative research methods, including ethnographic research, interviews with artisans, designers, and fashion entrepreneurs, and content analysis of fashion collections inspired by tribal aesthetics, the study provides a comprehensive examination of the interplay between tribal attire and regional fashion. The findings highlight the potential of tribal fashion in promoting sustainable and ethical fashion practices while preserving indigenous identity.